A comparison of collection development policies of selected university libraries - Santos, Kristine Marie P. (Institute of Library and Information Science, University of the Philippines Diliman, 2005)
The Philippine boasts of being the only Christian nation in Asia. In addition to the Christian majority, there is a vigorous 4 percent Muslim minority, concentrated in the southern islands of Mindanao, Sulu, and Palawan, scattered in isolated mountainous regions and the remaining 2 percent non-Western, indigenous beliefs and practices of those (Miller, 1996).A variety of sects like the Roman Catholic, Muslims, Protestants and the fundamentalist Christian groups, such as Jehovah's Witnesses and the Seventh Day Adventists, the Iglesia ni Kristo and Rizalists have emerged. As a result to these, these various religions established numerous colleges and universities. To name a few: for the Catholics, University of Sto. Tomas, Ateneo de Manila University, San Beda College, Holy spirit, etc.; for the protestants, Philippine Christian University, Trinity College and Silliman University, etc.; for the Iglesia ni Kristo, the New Era University.